KAJIAN KRITIS TENTANG AKULTURASI ISLAM DAN BUDAYA LOKAL - Muhammad Alqadri Burga (IAIN Kendari, 2019)
This article discusses acculturation of Islam and local culture in Indonesia which is focused on three main issues, namely 1) the form of acculturation of Islam and local culture; 2) the process of acculturation of Islam and local culture; and 3) the implications of acculturation of Islam and local culture towards the Islamic understanding of the ummah in Indonesia. This type of research is library research whose data are collected through documentation and analyzed using content analysis method. The results showed that acculturation of Islam and local culture was seen in traditional ceremonies, arts and architecture, and community value systems. Acculturation of Islam and local culture occurs because Islam has a universal side of meeting the local culture of the archipelago which requires affiliation and gets social support to develop. Acculturation of Islam and local culture in Indonesia resulted in the practice of local Islam which had implications for the emergence of three Islamic ideologies, namely traditionalist Islam, modernist Islam, and puritanical Islam. This study has implications for the teachings of Islam containing complete civilization, so it is necessary to do the Islamization of culture in the practice of local Islam in order to maintain the purity of Islamic teachings without losing the element of local culture. The philosophical meaning in the ritual symbols of traditional ceremonies must be interpreted according to Islam. This is an effort to purify the faith while accommodating local culture.